Rheumatoid Arthritis and Cardio-Cerebrovascular Disease: A Mendelian Randomization Study - Qiu, Shizheng; Li, Meijie; Jin, Shunshan; Lu, Haoyu; Hu, Yang (Frontiers in Genetics, 2021)
Significant genetic association exists between rheumatoid arthritis (RA) and cardiovascular disease. The associated mechanisms include common inflammatory mediators, changes in lipoprotein composition and function, and immune responses, etc. However, the causality of RA and cardiovascular disease remains unknown. Herein, we performed Mendelian randomization (MR) analysis using a large-scale RA genome-wide association study (GWAS) dataset (462,933 cases and 457,732 controls) and six cardio-cerebrovascular disease GWAS datasets, including age angina (461,880 cases and 447,052 controls), hypertension (461,880 cases and 337,653 controls), age heart attack (10,693 cases and 451,187 controls), abnormalities of heart beat (461,880 cases and 361,194 controls), stroke (7,055 cases and 454,825 controls), and coronary heart disease (361,194 cases and 351,037 controls) from UK biobank. We further carried out heterogeneity and sensitivity analyses. We confirmed the causality of RA with age angina (OR = 1.17, 95%CI: 1.04-1.33, P = 1.07E-02), hypertension (OR = 1.45, 95%CI: 1.20-1.75, P = 9.64E-05), age heart attack (OR = 1.15, 95%CI: 1.05-1.26, P = 3.56E-03), abnormalities of heart beat (OR = 1.07, 95%CI: 1.01-1.12, P = 1.49E-02), stroke (OR =1.06, 95%CI: 1.01-1.12, P = 2.79E-02), coronary heart disease (OR = 1.19, 95%CI: 1.01-1.39, P = 3.33E-02), contributing to the understanding of the overlapping genetic mechanisms and therapeutic approaches between RA and cardiovascular disease.